Un sociologue des religions en occitanisme, Jean (-Baptiste) Séguy - Philippe Gardy (Lengas)
Jean Séguy (1925-2007), a researcher at the CNRS, devoted a significant part of his time for a period of fifteen years, in parallel with his more "official" career as a sociologist of internationally recognized religions, to research in the Occitan field. This change led him to become a defender of the Occitan language, as Jean-Baptiste (or Joan-B.) Séguy: he began to learn this language that he only knew by hearsay initially, made it his other research language alongside French, and even went as far as becoming an Occitan writer, through critical, journalistic or fictional poems and proses. Through various unpublished or little-known documents, particularly letters, we try to describe the main features of this "Occitan temptation" and we examine the meaning of this attachment, to which he seems to have remained faithful until his last days.